Secukinumab - first in class interleukin-17A inhibitor for the treatment of psoriasis - Kiran Godse (Wolters Kluwer Medknow Publications, 2017)
Psoriasis is a complex inflammatory disease that occurs in genetically susceptible individuals and presents with the development of erythematous scaly plaques on the skin. Interleukins (ILs) in the Th17 pathway play a pivotal role in the pathogenesis of psoriasis and have thus become targets for recent biologic drug development. Secukinumab is a human monoclonal IgG1k antibody that has been developed to target and block the actions of IL-17A. Secukinumab recently approved for use as first-line systemic therapy in a patient with moderate to severe psoriasis has been studied first in psoriasis before other diseases. Both Phase II and III clinical trials have demonstrated the effectiveness of secukinumab in the treatment of moderate-to-severe plaque psoriasis, and it has demonstrated superiority to other comparable biologics on the market, including the tumor necrosis factor inhibitor etanercept. Secukinumab has also shown superiority to ustekinumab, a relatively recent biologic introduced for the treatment of psoriasis. Besides demonstrating better efficacy compared to etanercept and ustekinumab, secukinumab has also demonstrated a greater impact of the quality of life of patients with a comparable safety profile. Secukinumab shows great promise in having a tremendous impact on the treatment of plaque psoriasis based on its ability to produce similar, if not better, clinical outcomes than other biologic antipsoriasis medications.